2018
DOI: 10.1016/j.ccell.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

SET1A-Mediated Mono-Methylation at K342 Regulates YAP Activation by Blocking Its Nuclear Export and Promotes Tumorigenesis

Abstract: YAP, a key effector of Hippo pathway, is activated by its translocation from cytoplasm to nucleus to regulate gene expression and promote tumorigenesis. Although the mechanism by which YAP is suppressed in cytoplasm has been well-studied, how the activated YAP is sequestered in the nucleus remains unknown. Here, we demonstrate that YAP is a nucleocytoplasmic shuttling protein and its nuclear export is controlled by SET1A-mediated mono-methylation of YAP at K342, which disrupts the binding of YAP to CRM1. YAP m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 52 publications
4
98
0
Order By: Relevance
“…Together with these studies, our current work further demonstrates a complicated machinery for fine and tight control of YAP activity under various cellular contexts. Interestingly, some negative regulators of YAP, such as MST4 kinase characterized here, and the reported SET1A (Fang et al, 2018), RUNX3 (Qiao et al, 2016), and OTUD1 (Yao et al, 2018), were found to be down-regulated in different cancer specimens and to be associated with poor prognosis. Perhaps dysregulation of these YAP-related tumor suppressors could explain the hyperactivation of YAP in cancer cells without apparent change of the classic Hippo kinase cascade.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Together with these studies, our current work further demonstrates a complicated machinery for fine and tight control of YAP activity under various cellular contexts. Interestingly, some negative regulators of YAP, such as MST4 kinase characterized here, and the reported SET1A (Fang et al, 2018), RUNX3 (Qiao et al, 2016), and OTUD1 (Yao et al, 2018), were found to be down-regulated in different cancer specimens and to be associated with poor prognosis. Perhaps dysregulation of these YAP-related tumor suppressors could explain the hyperactivation of YAP in cancer cells without apparent change of the classic Hippo kinase cascade.…”
Section: Discussionmentioning
confidence: 50%
“…The Hippo–YAP pathway can respond to a wide range of stress signals, eventually leading to the manifestation of different states of YAP-dependent gene transcription. Recently, a burst of studies have identified various types of PTMs including ubiquitination, methylation, and O-GlcNAcylation to regulate YAP activation in Hippo-independent manners (Fang et al, 2018; Peng et al, 2017; Yao et al, 2018; Zhang et al, 2017, 2019). Together with these studies, our current work further demonstrates a complicated machinery for fine and tight control of YAP activity under various cellular contexts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[316][317][318][319][320] Ubiquitination in the Hippo-YAP signaling pathway In mammals, the Hippo signaling pathway can also maintain CSC stemness, regulate cell growth, control the size of organs and take part in tumorigenesis. 321,322 Ubiquitination also plays an important role in regulating the Hippo signaling pathway, with a variety of E3 ligases being identified. For example, CRL4DCAF1 negatively regulates the Hippo signaling pathway by ubiquitinating and degrading Lats1 while promoting the monoubiquitination of Lats2 and inhibiting its activity.…”
Section: Nanog Ubiquitinationmentioning
confidence: 99%